Hospital Waste Management and Environmental Problems in India - Mohankumar, S. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTS The main purpose of this paper is to give a view of the hospital waste management and environmental problem in India. The objective of this study is to analyze the health care waste management system, including practices and compliances. Most countries of the world, especially the developing countries, are facing the grim situation arising out of environmental pollution due to pathological waste arising from increasing populations and the consequent rapid growth in the number of hospital units. In India, there are about 6 lakhs hospital beds, over 23,000 primary health centers, more than 15,000 small and private hospitals. In India, the Biomedical Waste (Management and Handling) Rules 1998 make it mandatory for hospitals, clinics, and other medical and veterinary institutes to dispose of bio medical wastes strictly according to the rules. The few studies on bio medical waste management from India have established that hospitals did not manage health care waste properly. The hospital waste management sector market revenue (2008) is 8% of the total waste management revenue in India expected growth in next 5-6 years is around 20%.There are many institutions which pollute the environment but recently the ignored field which produce the pollution by way of hospital wastes and attracts the attention of the environmentalists are the hospitals, dispensaries, medical shops, medical clinics of doctors and other paramedical staff. Safe handling, segregation, storage, subsequent destruction and disposal of hospital waste ensure mitigation and minimization of the concerned health risks involved through contact with the potentially hazardous material, and also in the prevention of environmental contamination. Mismanagement of health care waste disposal cause dangerous infection and posses a potential threat to the surrounding environment, persons handling it and to the public. In the past, medical waste was often mixed with household waste and disposed of in municipal solid waste landfills. In recent years, increased public concerns over the improper disposal of health care waste have led to a movement to regulate the waste more systematically and stringently by the Indian government. Waste minimization and recycling are still not well promoted, which results in significant amounts.